A template for promoting energy conservation in Nigeria’s residential sector - Umoh, Edwin; Bande, Yahaya (International Journal of Sustainable Energy Planning and Management, 2021)
Energy conservation is an all-encompassing principle (building economics, behavioural, technological and educational) whose cumulative effects can result to improvement in energy access, energy availability and sufficiency, quality of life and retractive impacts on climate change and reduction in carbon footprint of a country. With the current global realities of COVID-19 pandemic, energy conservation has become one of the systemic resilience strategies necessary to manage dwindling energy supplies and financial shocks. However, as simplistic as it sounds, energy conservation as a behaviour of household consumers is a complex phenomenon that has persisted throughout the century. While strategic policies and long-term planning have promoted and re-orient consumers in some developed and developing countries towards energy conservation behaviour, there is no paradigm shift from energy wastage to energy conservation among consumers in Nigeria’s residential sector. This paper therefore discusses the factors that constrains energy conservation among household electricity consumers, unearths precursors and enablers of energy conservation with peculiar appeal to Nigeria. Policy implications and strategies of entrenching energy conservation culture are also outlined.